The effect of vitamin D deficiency and vitamin D supplementation on the risk of cardiovascular diseases - Romina Ghassab (Family Medicine & Primary Care Review, 2021)
Studies revealed an association between vitamin D deficiency and the frequency of cardiovascular diseases and their risk factors. This review is aimed at summarizing evidence for the association of vitamin D deficiency and vitamin D supplementation with the risk of cardiovascular diseases. The data was collected by surfing the Pubmed, Cochrane Central Registry and EMBASE databases for appropriate and related studies. Search terms included: "Vitamin D", "cardiovascular diseases", "CVD", "calcitriol" and "1,25-dihydroxy vitamin D". The abstracts of the discovered articles were reviewed, and the full texts of the articles that met the criteria were then evaluated to be used for the study. The large number of clinical trials, cross-sectional, prospective and systematic review studies are evidence that vitamin D deficiency is associated with most cardiovascular disease (CVD) risk factors and with the pathogenesis of CVD. However, with regard to the clinical trial studies evaluated in this work, vitamin D supplementation did not decrease the occurrence of cardiovascular events.